(untitled) (Student Conference Proceedings, 2025)
The ISO/IEEE 11073-SDC standard defines architecture and protocol on interoperability between manufacturer-independent medical devices. In this paper, a prototype implemented this standard to process clinical trend data using Apache Kafka for data storage and GraphQL for its interface. The proposed prototype demonstrated real-time and historical data connected to 100 simulated devices. In the evaluation, the processing time of trend during high-load setting has occasional outliers, however its median is relatively low. A single historical trend query with varied payload and real-time subscriptions were effectively executed, meanwhile simultaneous queries from multiple devices caused high latency due to resource contention.